2008
DOI: 10.21273/hortsci.43.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of Soil Moisture in Drip-irrigated Vineyards

Abstract: In arid and semiarid areas, wine grapes are frequently managed using regulated deficit irrigation (RDI) to control vegetative growth. To understand the distribution of soil moisture using RDI in a drip-irrigated vineyard, we collected soil samples after several irrigation events around six drip emitters in two ‘Cabernet Sauvignon’ and two ‘Merlot’ vineyards from late July through Mar. 2002 and 2005. The March sampling depicts soil moisture status before budbreak after winter precipitation. Soil samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…water use at a higher level, (i.e., more efficacious) than weekly irrigation by conventional means. Water distribution in the irrigated zones was within 10 to 30 cm from the drippers as reported by other researchers (Badr and Abuarab, 2013;Davenport et al, 2008).…”
Section: Root Distribution Patternssupporting
confidence: 80%
See 1 more Smart Citation
“…water use at a higher level, (i.e., more efficacious) than weekly irrigation by conventional means. Water distribution in the irrigated zones was within 10 to 30 cm from the drippers as reported by other researchers (Badr and Abuarab, 2013;Davenport et al, 2008).…”
Section: Root Distribution Patternssupporting
confidence: 80%
“…Our own results (Kadyampakeni, 2012) and those of Zhang et al (1996) showed that tree uptake should be greater in the 0-to 15-cm soil layer than lower horizons due to higher root density in the range of 55% to 67% on length basis and 70% to 75% on weight basis in the top 15 cm. Davenport et al (2008) also observed that soil moisture distribution for drip-irrigated vineyards was adequate in the 0-to 45-cm depth and within 20-to 40-cm radius, either diagonal or perpendicular to the drip line. Our observations are also in agreement with Goldberg et al (1971) who found that soil moisture resulting from drip irrigation was two-dimensional, with moisture contents high along and beneath the row and decreasing laterally.…”
Section: Root Distribution Patternsmentioning
confidence: 73%
“…Essentially, as the irrigation water and, when fertilized, the nutrients carried in it move out to a certain point, the soil then dries and "strands" the nutrients into a zone where there is no longer enough soil moisture to move them, thus building up the salts. This is supported by previous work looking at water and nutrient movement in drip-irrigated vineyards in central Washington that informs the recommendations for where to collect soil samples for nutrient analysis (Davenport et al, 2008(Davenport et al, , 2011Singer et al, 2018).…”
Section: S Ilmentioning
confidence: 55%
“…Before the first treatment application, 16 polyvinyl chloride neutron probe access tubes were installed, one per plot, between sample vines two and nine. Each tube was located within 0.2 to 0.4 m away from a drip emitter on an %45°diagonal from the drip tubing (Davenport et al, 2008). The tubes were made from 1-m lengths in 2011 and 1.5-m lengths in 2012, 2013, and 2014 of 5-cm-diameter pipe with a 2-mm wall thickness (Ridgeline Pipe Manufacturing, Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%